Objective and quantitative evaluation of intellectual productivity under control of room airflow. (February 2019) - Obayashi, Fumiaki; Miyagi, Kazune; Ito, Kyoko; Taniguchi, Kazuhiro; Ishii, Hirotake; Shimoda, Hiroshi
Abstract: In order to design a work environment that improves office workers' intellectual productivity, the authors have focused on airflow, which is a key factor in thermal environments. An airflow control method that improves the degree of concentration is proposed, and its effectiveness is evaluated objectively and quantitatively by evaluative experiments. The designed airflow environment is composed of two airflow components: a stimulative airflow and a mild airflow. In this experiment, cognitive tasks are given to participants. The concentration time ratio (CTR), which is a quantitative and objective evaluation index of the degree of concentration, is measured. The results show that the average CTR under the proposed airflow condition is 61.1%, while that under the no airflow condition is 54.6%. The proposed airflow control shows a significant improvement in CTR, with an increase of 6.5% (p < 0.001). Consequently, our findings suggest that intellectual work can be performed better in an environment that fosters a high concentration time ratio. Highlights: Indoor environmental control that improves concentration during intellectual work. Objective/quantitative index of concentration to evaluate intellectual productivity. Proposing concentration-improving airflow composed of two types of control. Effectiveness of the proposed airflow control validated by subject experiment. Degree of concentration improved by 6.5% under the airflow control (p < 0.001).